Peran Metode Pembelajaran Aktif dalam Pendidikan Islam : Meningkatkan Keterlibatan Siswa di SMP IT Yaspida - Muhamad Wisnu; Muhamad Rafli; Ari Rahmatullah Fauzi (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
In an increasingly competitive era of education, student engagement in the learning process is very important. Active learning methods, which prioritize active student participation, have been proven to improve motivation and learning outcomes. This study aims to explore various active learning methods in the context of Islamic education and their impact on student engagement. Through data analysis from various case studies, this study found that the application of active learning methods can significantly increase student engagement.